Pengembangan Media Pembelajaran Berbasis Aplikasi Kinemaster Pada Pembelajaran Tematik Terpadu di Kelas III Sekolah Dasar - Vira Amelia; Arwin Arwin (Universitas Negeri Padang, 2020)
The development of the times demands that humans be more progressive, thus students are required to find information independently from the results of their interactions with the learning environment. Learning media are used to streamline messages so that a learning environment is created conducive. In fact, the use of learning media is still conventional, does not vary, and the use of digital media is still very minimal. This type of research is research and development using the 4D model. However, the steps taken are only define, design, and development. The resulting product declared very valid with the average feasibility of learning media is 95%, with details of the feasibility of material 93.3%, media 96.7%, and language 95%. The results of teacher and student responses were stated to be very practical, namely 92.5% and 95.25%. Thus, learning media based on the Kinemaster application in integrated thematic learning in class III SD Negeri 36 Koto Panjang are declared very valid and very practical.